If a b c are in ap then the value of (a+2b-c) (2b+c-a)(a+2b+c) is A.4a B.2a C.3 D. None of these
Answers
Answered by
4
Answer:
answer for the given problem is given
Attachments:
![](https://hi-static.z-dn.net/files/d3f/de8338f7f2846fc650d243b3fa5e6bae.jpg)
Answered by
4
ATQ:
a, b and c are in a AP.
To find:
(a + 2b - c) (2b + c - a) (a + 2b + c)
Solution:
First term of the AP → a
Second term of the AP → b
Third term of the AP → c
We know that b can be expressed as the sum of the preceeding term (a) and the succeeding term (c) divided by two since they all have a common difference.
Therefore;
⇒ (a + 2b - c) (2b + c - a) (a + 2b + c)
Substitute the value of 2b = a + c above.
⇒ (a + a + c - c) × (a + c + c - a) × (a + c + 2b)
⇒ (a + a) × (c + c) × (2b + 2b)
⇒ (2a) × (2c) × (4b)
⇒ (2) × (2) × (4) × (a) × (b) × (c)
⇒ 16abc
16abc isn't provided in the options, therefore, your answer will be (D) None of these.
Similar questions